2015
DOI: 10.1111/jvim.12511
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nociceptive Ligands in Canine Osteosarcoma

Abstract: BackgroundCanine osteosarcoma (OS) is associated with localized pain as a result of tissue injury from tumor infiltration and peritumoral inflammation. Malignant bone pain is caused by stimulation of peripheral pain receptors, termed nociceptors, which reside in the localized tumor microenvironment, including the periosteal and intramedullary bone cavities. Several nociceptive ligands have been determined to participate directly or indirectly in generating bone pain associated with diverse skeletal abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…38 Specifically in OSA of dogs, PGE 2 is increased in both canine OSA cell lines and in naturally occurring tumors, 39 COX-2, microsomal PGE 2 synthase-1, and PGE 2 receptor are demonstrated to be increased in OSA lesions using immunohistochemistry staining, 40 and OSA cells from dogs secrete PGE 2 . 41 Our findings of increased PGE 2 in dogs with OSA are in accordance with these previous reports, and emphasize the ability of PGE 2 to induce immunopathology in OSA.…”
Section: Discussionsupporting
confidence: 93%
“…38 Specifically in OSA of dogs, PGE 2 is increased in both canine OSA cell lines and in naturally occurring tumors, 39 COX-2, microsomal PGE 2 synthase-1, and PGE 2 receptor are demonstrated to be increased in OSA lesions using immunohistochemistry staining, 40 and OSA cells from dogs secrete PGE 2 . 41 Our findings of increased PGE 2 in dogs with OSA are in accordance with these previous reports, and emphasize the ability of PGE 2 to induce immunopathology in OSA.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings complement and extend existing knowledge regarding ET A R signaling in OS, and in particular the relevance of ET‐1 in the biology of canine OS . As indicated by the protein expression studies, canine OS cell lines and spontaneous tumor samples co‐express both receptor and cognate ligand, findings that substantiate the potential existence of a paracrine or autocrine signaling pathway that could be subverted by malignant osteoblasts.…”
Section: Discussionsupporting
confidence: 81%
“…For example, primary afferent sensory neurons from the bone are restricted to specific A-delta and C-fibers [46]. In addition, recent research identified that canine OSA cells express and secrete nerve growth factor, endothelin-1 and prostaglandin E 2 which potentially participate in malignant bone pain [9]. Finally, microfracture can result from progressive osteolysis by activated osteoclasts [7].…”
Section: Discussionmentioning
confidence: 99%
“…These clinical signs tend to progress over time and patients become severely affected with altered function and QoL [7,8]. The actual incidence and characteristics of cancer pain in dogs remain unknown [9]. Nevertheless, given that dogs frequently present with advanced-stage cancer at initial evaluation and have similar cancer biology when compared with humans [10], it is reasonable to presume that canine patients experience a similar pain profile [2].…”
Section: Introductionmentioning
confidence: 99%